Globalization As a Factor Influencing Threats in the 21st Century - Piotr MAŚLOCH; Henryk WOJTASZEK; Ireneusz MICIUŁA; Mateusz ZIĘTARSKI; Miłosz GAC (Communications of International Proceedings, 2022)
Globalization is one of the important factors that affects security. Before the Covid process, increasing globalization was noticeable, now it has slightly decreased. This article deals with globalization as a redistribution of its costs and benefits. The following factors were analyzed: political, social and economic influencing the functioning of globalization. Opening up to the world is a faster opportunity for many countrieseconomic development. No wonder then that globalization has become the subject of many scientific studies that focus on these opportunities, but also threats that accompany it. The analysis undertaken in the countries of the European Union shows that the situation related to covid strongly influenced the development of the economy, and hence the globalization - slowing down its process.
Keywords: Management; Globalization; Factors; Threats; Security